The self-perceived needs of adolescents with suicidal behaviour: a scoping review. - Looijmans, Milou; van Bergen, Diana; Popma, Arne; van Eijk, Nikki; Mérelle, Saskia; van Veen, Sisco; Hawton, Keith; Gilissen, Renske (European Child & Adolescent Psychiatry, 2025)
Suicidal behaviour in adolescents is a major public health problem. Much research on this issue has focused on epidemiology and risk factors for suicidal behaviour, paying less attention to the self-perceived needs of adolescents. However, to increase engagement in suicide prevention, it is important to include the views of adolescents. A scoping review was performed to identify the available empirical study findings, of any study design, related to the self-perceived needs of adolescents with suicidal behaviour. The literature databases Medline, Embase, Psycinfo, CINAHL, ERIC, Scopus, and Web of Science were searched. Twenty-nine studies from 14 predominantly Anglo countries were included in the scoping review. The review showed that girls were overrepresented and that studies predominantly used qualitative approaches. The identified needs of adolescents with suicidal behaviour can broadly be grouped into needs related to the following areas: the importance of connecting with other people; adolescents' self-help strategies and personal growth after self-harm; mental healthcare; school or study programs; and needs related to society in relation to taboo on suicidal behaviour. Prevention of suicidal behaviour in adolescents will need to focus on development and strengthening of interventions fitting the needs of adolescents in these areas.